A leaf-like structured ITO conductive transparent thin film from visible to near-infrared region with enhanced stability. Issue 6 (June 2022) - Cao, Lili; Wang, Tao; Ma, Kexin; Zhang, Zhiwei; Luo, Fei; Zhou, Haitao; Liu, Dabo; Miao, Min; Luo, Bingwei; Xu, Yi
Abstract: ITO thin films as the optical and electrical windows to transform photons and charges have been applied in many areas. Here, a leaf-like structured particle is composed of small particles growing along three different orientations leading to low thermal stress accompanied by well transmittance (85%) in a wide wavelength range from visible to near-infrared region and a narrowed band gap 3.07 eV. The evolution of structure and electronic performance was studied to obtain the low resistivity (12 μΩ m) and enhanced stability of the film (1000 °C). The leaf-like structure can be maintained under 600 ℃ and the electrical properties can be modified in He and N2 atmosphere, owing to the reduced defects, increased concentration of Sn and carrier mobility. Although the structure has changed after being annealed at 1000 °C in N2, the thin film performs excellent electrical properties (−3.44 × 10 20 cm −3 and 28 cm 2 V −1 s −1 ).